Pengembangan Sumber Daya Manusia Pada Kantor Distrik Homeyo Kabupaten Intan Jaya Papua - Bagubau, Abraham; Areros, William A; Goni, J H (JURNAL ILMIAH SOCIETY, 2015)
Human resource development that occurs in pemerrintah personnel and the general public can not be separated from factors outside or from within. Homeyo District is one of the names of the seven district in Intan Jaya district. Human resource development that occurs in the government and public officials Homeyo District mainly because of education, knowledge. Factors driving force includes contact with the culture that comes from the West, another public system open, heterogeneous population consisting of several genera such as Bagubau, Bagau, Belau, Kobogau, Selegani, Tipagau, Mayani, Hagimuni, Miagoni, Migau, Wandagau, Japugau, Duwitau, Zanambani, Wamuni, Jagani, Holombau, as well as future-oriented society, but other things, that hinder the process of development of human resources, among others, is to have a level of education and knowledge are low both education and nono fromal fromal. Â Keywords: Development, Human Resources, Education, Training